MANAGEMENT OF FIBROMYALGIA: A COMPREHENSIVE REVIEW OF ESTABLISHED AND EMERGING THERAPEUTIC STRATEGIES AND PATHOPHYSIOLOGICAL MECHANISMS - Katarzyna Garncarz; Aleksandra Marek; Krzysztof Jamroch; Karolina Dziki; Wiktoria Dybizbańska; Zofia Nowakowska; Agnieszka Burzej; Mateusz Kacalak; Maciej Komenda; Julia Szklarska-Komenda (International Journal of Innovative Technologies in Social Science, 2025)
Our review article summarizes current knowledge on the clinical features, underlying mechanisms, and therapeutic strategies for fibromyalgia. Recent evidence identifies fibromyalgia as a complex neuroimmune and neuroplastic disorder driven primarily by central sensitization, with additional contributions from peripheral nociceptor dysfunction, low-grade inflammation, neuroendocrine alterations, and psychosocial factors. These mechanisms explain the heterogeneous symptom profile, including widespread pain, fatigue, sensory hypersensitivity, cognitive impairment, and mood disturbances, suggesting the existence of distinct phenotypic subgroups. Current pharmacological treatments, such as tricyclic antidepressants, SNRIs, gabapentinoids, and sublingual cyclobenzaprine, offer moderate and variable benefits, while emerging agents targeting novel pathways remain under investigation. Non-pharmacological interventions, including structured exercise, cognitive-behavioral therapy, and selected complementary techniques, demonstrate comparable effectiveness, particularly within multidisciplinary care. Overall, the literature highlights the need for personalized, holistic management and further biomarker-driven studies to advance precision-medicine approaches in fibromyalgia.